Synthesis and Evaluation of the Analgesic and Anti-inflammatory Activity of New 3(2H)-Pyridazinone Derivatives - Gökçe, Mehtap; Şahin, Mustafa Fethi; Küpeli, Esra; Yeşilada, Erdem (Arzneimittelforschung, 2004)
A series of 6-substituted-3(2H)-pyridazi-none derivatives were synthesized and evaluated for analgesic and anti-inflammatory activities. The structures of these new pyridazinone derivatives were confirmed by their IR, 1H-NMR spectra and elementary analysis.Analgesic and anti-inflammatory activities of the title compounds have been evaluated. Four of the ten tested compounds possessed significant analgesic effects in the phenylbenzoquinone-in-duced writhing test (PBQ test). The most active derivatives 8a, 8b, 8d, 8e were void of gastric ulcerogenic effect or acute toxicity at the maximal dose (200 mg/kg p.o.). In the carrageenan-induced paw edema model, compound 8d (6- [ 4- (2-fluoro-phenyl) piperazin-1 -yl] - 3 (2H) -pyridazinone) showed anti-inflammatory activity similar to that of the standard drug Indometacin (CAS 53-86-1). A significant dependence of the anti-inflammatory effect on the substituents was observed. The pharmacological study of these compounds confirms that modification of the chemical group at position 6 of the 3(2H)-pyridazinone ring influences analgesic and anti-inflammatory activities.
Keywords: 3(2H)-Pyridazinones, analgesic activity, anti-inflammatory activity